University Pedagogy Based on Generic Competencies to Develop Critical Thinking Skills in Students of the National University of San Martín - López-Novoa, Ibis (2020)
This article addresses the issue of university pedagogy based on generic skills to develop critical thinking skills, the objective was to measure the influence of university pedagogy based on generic skills in the development of critical thinking skills in students in the I cycle from the National University of San Martín, 2019. The research was quantitative, quasi-experimental design, experimental type, the population was made up of 420 students, the sample determined by 180 students, to whom a questionnaire was applied as a survey to Collect the information. The results show that in the experimental group (HG:μpostestμpretest-H0: μpostest= μpretest) the null hypothesis is rejected, therefore the scores are different, the scores are higher in the post test compared to the pre test (P sig <0.05 -0.000 <0.05) in this case the null hypothesis is rejected and the alternative hypothesis is accepted where the effectiveness of university pedagogy based on generic competencies in the development of critical thinking skills in I students cycle of the National University of San Martín, 2019; that is the post test scores are high.